Evaluation of Risk Governance as an Effort to Manage Risk in VWX Public Institutions - Isnain, Safril Burhan; Lisdiono, Purwatiningsih (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p19, 2025)
Public institutions in optimizing the achievement of the vision, mission, goals and objectives of the organization need to optimize the implementation of good risk governance. This study aims to evaluate the implementation of risk governance in VWX public institutions with the IRGC framework. Data collection uses a qualitative case study method with primary data in the form of interviews and secondary data in the form of regulations and documents related to risk management. The results showed that good risk governance will make the organization run effectively in optimizing risk handling. The context of the IRGC framework has been implemented by VWX institutions in risk governance. However, the context of Organizational Capacity (human resource management) and Social Climate is still not optimally implemented, hindering the goal of increasing organizational risk awareness culture. Keywords: Risk; Risk Management; Risk Governance; Public Institutions